A systematic review of the effectiveness of promoting water intake to reduce sugar‐sweetened beverage consumption - Dibay Moghadam, Sepideh (Obes Sci Pract, 2020)
OBJECTIVE: To examine whether the promotion of water intake could reduce sugar‐sweetened beverage (SSB) consumption or purchases independent of interventions that target SSBs. METHODS: Seven databases were systematically searched. Included studies used water promotion as the primary intervention; used a controlled trial, single group pre‐post, or prospective cohort study design; included a measure of SSB consumption or purchase; enrolled human participants of any age who lived in high‐income or middle‐income countries; contained original data; and appeared in a peer‐reviewed English‐language article published from 1 January 2000 to January 4, 2019. The search yielded 7068 publications, from which 108 were chosen for full‐text review. Seventeen were included in this review. RESULTS: Nine of the 17 studies were randomized controlled trials, six were nonrandomized controlled trials, and 2 were single‐group pre‐post studies. Participants were primarily children and adolescents. Interventions included water provision, education or promotion activities. Ten of 17 studies were at low or some/moderate risk of bias. Seven studies showed a statistically significant decrease in SSB consumption of which only 2 were at low or some/moderate risk of bias. CONCLUSIONS: This review found limited evidence that interventions aimed solely at increasing water consumption reduce SSB intake. Further research is needed to investigate whether interventions that combine water promotion and SSB reduction strategies could be synergistic for reducing SSB intake.